Visual preferences and their effect on reading performance in children with dyslexia and typical readers - Pellicer Magraner, Ana; Máñez-Carvajal, Carlos; Zafra-Delgado, Carla; Cervera-Mérida, José Francisco (Revista de Investigación en Logopedia, 2025)
The visual configuration of text influences the reading experience and can affect performance in this skill, particularly in children with dyslexia. This study examines whether the typographic preferences of children with dyslexia differ from those of typically developing readers and evaluates the impact of personalized text formatting on reading fluency and comprehension. A total of 70 children (30 with dyslexia and 30 typical readers) aged 7 to 12 years were assessed. Participants read two on-screen texts, first in a standard format and then in a format customized according to their preferences. Variables such as background and text color, typeface, font size, margin size, line spacing, and letter spacing were analyzed. Reading fluency and comprehension were measured before and after customization. Results indicate that both groups selected similar configurations, avoiding high text density and prioritizing high contrast. The only significant difference between groups was the font size selected, which was larger in the dyslexia group. Text personalization slightly improved reading fluency in both groups, though without a differential effect for the dyslexia group. No improvements were found in reading comprehension. These findings suggest that text customization may facilitate decoding and reading speed but does not impact comprehension. Although no specific benefits were observed for children with dyslexia, optimizing the visual presentation of text may contribute to a more comfortable and motivating reading experience.